Answer: 16-p=C
Step-by-step explanation:
p is price of the wallet and it has to be either less than or equal to the 16 dollars spending money. And that result will equal C which represent the change or what's left after spending unknown amount from 16
Answer:
4/5 chance
Step-by-step explanation:
There are 4 numbers that fit the rule, 1, 3, 4, 5, since all of them are either odd or greater than 3. There will be a 4/5 chance of picking one.
we have
![3x^{2} + 18x - 8 = 0](https://tex.z-dn.net/?f=%203x%5E%7B2%7D%20%2B%2018x%20-%208%20%3D%200%20%20)
Step ![1](https://tex.z-dn.net/?f=%201%20)
Move the constants to the right side
![3x^{2} + 18x = 8](https://tex.z-dn.net/?f=%203x%5E%7B2%7D%20%2B%2018x%20%3D%208%20%20)
Step ![2](https://tex.z-dn.net/?f=%202%20)
Factor 3 out of the variable terms
![3(x^{2} + 6x) = 8](https://tex.z-dn.net/?f=%203%28x%5E%7B2%7D%20%2B%206x%29%20%3D%208%20%20)
Step ![3](https://tex.z-dn.net/?f=%203%20)
Add
to both sides of the equation
![3(x^{2} + 6x+9) = 8+27](https://tex.z-dn.net/?f=%203%28x%5E%7B2%7D%20%2B%206x%2B9%29%20%3D%208%2B27%20%20)
![3(x^{2} + 6x+9) = 35](https://tex.z-dn.net/?f=%203%28x%5E%7B2%7D%20%2B%206x%2B9%29%20%3D%2035%20%20)
Step ![4](https://tex.z-dn.net/?f=%204%20)
Write the polynomial as a binomial squared
![3(x+3)^{2} = 35](https://tex.z-dn.net/?f=%203%28x%2B3%29%5E%7B2%7D%20%3D%2035%20%20)
therefore
the answer is
Factor 3 out of the variable terms.
The roots, zeros, or solutions (they all means same thing) of an equation are when you graph that equation, x-intercepts are the real roots, zeros, or solutions.
Or set the y equal to zero which does the same job.
Answer: 1
Step-by-step explanation:
First you need to multiply 3 x 3 (9), because that's all 3 squared means.
Now the equation should be 9x-6x+3=0
Next we need to combine like terms. Do 9x - 6x which should give you 3x
Now your equations should be 3x+3=0
Now for the somewhat harder part...
Under the three (the one without the x) write -3 and under the zero write the same thing. the +3-3 cancels out so just put a line or something across it.
0-3= -3
so now you should have...
3x=-3 ignore the 3x, at this point it's useless in getting the answer because it would cancel out.
-3 divided by -3 is 1 because a negative (-) divided by a negative (-) equals a positive (+).
The answer should be x = 1